2018
DOI: 10.1002/ecy.2370
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of leaf carbon exchange capacity across biomes at the continental scale

Abstract: Realistic representations of plant carbon exchange processes are necessary to reliably simulate biosphere-atmosphere feedbacks. These processes are known to vary over time and space, though the drivers of the underlying rates are still widely debated in the literature. Here, we measured leaf carbon exchange in >500 individuals of 98 species from the Neotropics to high boreal biomes to determine the drivers of photosynthetic and dark respiration capacity. Covariate abiotic (long- and short-term climate) and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 81 publications
(192 reference statements)
6
36
2
Order By: Relevance
“…Our results contradict this assumption, and provide a quantification of the temperature responses of both V cmax and R d that explicitly takes acclimation into account. Given that V cmax has been found to vary seasonally, and can be predicted using the temperature of the previous week (Smith & Dukes, ), a weekly to monthly acclimation time scale would be appropriate for LSMs to incorporate this process. It has also been shown that high growth temperature has a stronger negative impact on the instantaneous thermal response of V cmax than that of dark respiration (Smith & Dukes, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results contradict this assumption, and provide a quantification of the temperature responses of both V cmax and R d that explicitly takes acclimation into account. Given that V cmax has been found to vary seasonally, and can be predicted using the temperature of the previous week (Smith & Dukes, ), a weekly to monthly acclimation time scale would be appropriate for LSMs to incorporate this process. It has also been shown that high growth temperature has a stronger negative impact on the instantaneous thermal response of V cmax than that of dark respiration (Smith & Dukes, ).…”
Section: Discussionmentioning
confidence: 99%
“…First, thermal acclimation of net CO 2 assimilation consists of several processes (changes in photosynthetic capacity, photorespiration, and respiration in the light, as well as changes in stomatal conductance; Kattge & Knorr, ; Slot & Kitajima, ; Yamori et al, ). These responses could occur at different time scales, although recent evidence suggests that photosynthetic capacity and respiration may respond at similar time scales (Smith & Dukes, ). The response function A net ( T l ) (Equation ), condenses all these physiological mechanisms via a set of measurable parameters (Equation ) and their changes with acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of the theory relies on knowledge of photosynthetic capacity, which varies both among species and over time and space, in response to environmental conditions (Ali et al . ; Smith & Dukes ).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of these models, C 3 photosynthesis is simulated using well-established biochemical theory (Farquhar et al 1980). The applicability of the theory relies on knowledge of photosynthetic capacity, which varies both among species and over time and space, in response to environmental conditions (Ali et al 2015;Smith & Dukes 2018).…”
Section: Introductionmentioning
confidence: 99%